Kepemimpinan Jhon Calvin Yang Transformatif - Ali Matius (ICHTUS: Jurnal Teologi dan Pendidikan Kristiani, 2023)
Abstract: Calvin is a Transformative leader who brings many changes. The liberator of the people from wrong ideas (heresy), in which he also refers to himself as the reformer, a reformed theological architect. if Luther was the soldier who launched the opening shot of the Reformation, Calvin was the main expert who consolidated the results of Protestant progress. He tried to reform not only the doctrine and organization of the church, as did Luther, but also the socio-political order in accordance with the word of God. Calvin proved that he was a "complete leader" with strong characters, more comprehensive knowledge, and more special, and social and technical skills that were very reliable in his leadership. Proof of his reliability as a leader and realized by training / developing, education is celebrated as a center of education, thus giving birth to a new generation / leader. The superiority of Calvin's leadership is proven by the presence of new leaders who emerge and lead excellence in continuing his leadership. Calvin proved to be a smart, creative and effective shepherd. This can be seen in Calvin building a healthy and neatly arranged organization. This greatly supports the continuity of the institution / organization it leads. Calvin applies the science of leadership, management and administration well. So as to produce effective service performance and bring success to the church he leads. Calvin proves that the implementation of tasks is effective by delegating leadership tasks to the right people and with a definite system. And can be monitored, also evaluated.Keywords: Transformative Leader, Complete leader, Strong Characters, Comprehensive KnowledgeAbstrak: Calvin adalah pemimpin yang Transformatif yang membawa banyak perubahan. Pembebas umat dari faham yang salah (ajaran sesat), di mana Ia pun merujuk kepada diri-Nya sebagai sang reformator, seorang arsitek theologia reformasi. apabila Luther adalah prajurit yang meluncurkan tembakan pembukaan Reformasi, maka Calvin adalah pakar utama yang mengonsolidasikan hasil-hasil kemajuan Protestan. Ia berusaha mereformasi bukan hanya doktrin dan organisasi gereja, seperti yang dilakukan oleh Luther, tetapi juga tatanan sosial-politik sesuai dengan firman Allah. Calvin membuktikan bahwa diri-Nya adalah "Pemimpin lengkap" dengan karakter yang tangguh, memiliki pengetahuan yang komprehensif, dan khas lebih, serta kecakapan sosial dan teknis yang sangat andal dalam kepemimpinan-Nya . Pembuktian keandalan-Nya sebagai pemimpin dan diwujudkan dengan melatih/mengembangkan, para pendidikan di jenewa sebagai pusat pendidikan, sehingga melahirkan generasi /pemimpin baru. Keunggulan kepemimpinan Calvin ini terbukti dengan adanya pemimpin baru yang muncul dan memimpin secara unggul dalam meneruskan kepemimpinan-NyaKata kunci: Pemimpin Transformatif, karakter, pengetahuan